Remodelling the current practices in the teaching of science to improve its learning processes among students in Malaysian secondary schools. - Karpudewan, Mageswary
Science and technology are fundamental forces behind development of a country like Malaysia which aspires to achieve the status of fully developed country by the year 2020. For the nation to be progressive in all sectors it is imperative for the country to have significant numbers of researchers and scientists.